Serum Neopterin Concentration and Impaired Glucose Metabolism: Relationship With β-Cell Function and Insulin Resistance - Lee, Jie-Eun; Oh, Tae Jung; Moon, Jae Hoon; Park, Kyong Soo; Jang, Hak Chul; Choi, Sung Hee (Frontiers in Endocrinology, 2019)
Aim: The purpose of this study was to measure the serum neopterin according to glucose metabolism and to evaluate neopterin as a predictor of type 2 diabetes (T2D) in a hospital-based cohort. Methods: A 75-g oral glucose tolerance test (OGTT) was performed by people who visited the outpatient clinic in Seoul National University Bundang Hospital for suspected abnormal glucose tolerance or a strong family history of T2D. Neopterin was measured using an enzyme-link immunosorbent assay with baseline samples from the OGTT. Results: Neopterin was measured in 184 participants. Indices related to glucose metabolism such as the HOMA-IR, disposition index, etc. were calculated based on the results of the OGTT. The classifications for the 184 participants were: 24 (13%) had NGT, 89 (48.4%) prediabetes, and 60 (38.6%) T2D. Neopterin increased with deterioration of glucose metabolism (0.55 ± 0.25 vs. 0.58 ± 0.27 vs 0.67 ± 0.27 ng/ml, p = 0.041; NGT, prediabetes, and T2D, respectively). Neopterin also correlated with fasting plasma glucose, 30-min and 120-min glucose of OGTT and HbA1c (r = 0.251, 0.259, 0.184, and 0.270, all p < 0.05). The HOMA-IR and disposition index correlated with neopterin (r = 0.291 and –0.170, respectively, both p < 0.05). When combined with C-peptide level, neopterin was as powerful as HOMA-IR in predicting future T2D. Conclusion: Serum neopterin appears to be related to impaired insulin secretion and insulin resistance in the development of T2D. Further investigation of the relationship between neopterin and glucose metabolism would be helpful to understand the pathophysiology for the development of T2D.